A World in Disarray: American Foreign Policy and the Crisis of the Old Order - Richard Haass (Penguin Press; 1st. edition, 2017)
Things fall apart; the center cannot hold. The rules, policies, and institutions that have guided the world since World War II have largely run their course. Respect for sovereignty alone cannot uphold order in an age defined by global challenges from terrorism and the spread of nuclear weapons to climate change and cyberspace. Meanwhile, great power rivalry is returning. Weak states pose problems just as confounding as strong ones. The United States remains the worldâ€™s strongest country, but American foreign policy has at times made matters worse, both by what the U.S. has done and by what it has failed to do. The Middle East is in chaos, Asia is threatened by Chinaâ€™s rise and a reckless North Korea, and Europe, for decades the worldâ€™s most stable region, is now anything but. As Richard Haass explains, the election of Donald Trump and the unexpected vote for â€œBrexitâ€ signals that many in modern democracies reject important aspects of globalization, including borders open to trade and immigrants.